Ø£Ø«ÙŠØ± Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù‚ÙŠØ§Ø³ ÙÙŠ Ø§Ù„ØªÙ‚Ø§Ù† Ø§Ù„Ù†ØÙˆØ¹Ù„Ù‰ Ù‚Ø¯Ø±Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ziadah Hasanah; Ruwaida Hudatullah (Lughatu Ad-Dhat, 2021)
This study aims to determine the effect of learning using the measurement method on the grammar proficiency of students' reading ability, is there a difference in the learning outcomes between students who were treated using the measurement method and students who did not use the measurement method. This research was conducted in the Islamic High School of Bibidas in the period from August 26 to September 26, 2.19. This type of research uses quasi-experimental methods. The research sample consisted of 2. students in the eleventh class 1 for the control class, and their number reached 20 students in the class in the eleventh class 2 for the experimental one. The sampling technique is purposeful sampling that is selected based on the teacher's consideration. The research instrument used was a multiple choice test that was tested for validity and reliability. Data collection techniques in the form of observation, documentation and unstructured interviews, while the data analysis used by researchers is the use of independent sample test (t_tes test). The results showed that the measurement method applied to the experimental class can significantly affect the mastery of the language of grammar and the ability of students to read Arabic texts significantly in teaching Arabic. This can be seen by the average student learning outcomes taught using the measurement method. This is clear from the description of the data before the test, before applying the measurement method in the experimental class to get the average class 68.75, and the control class 43,... But after receiving treatment after the test, the experimental class reached a mean = 83.25, and the degree of control reached the mean = 61.50. While the results of data analysis using the t_test statistics obtained a value of t-calculation = 7.148 and t-table = 2.42.